If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(X + -2) = 1 Reorder the terms: 3x(-2 + X) = 1 (-2 * 3x + X * 3x) = 1 (-6x + 3xX) = 1 Solving -6x + 3xX = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Reorder the terms: -1 + -6x + 3xX = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -6x + 3xX = 0 The solution to this equation could not be determined.
| zy=301 | | 586+x=700 | | N+4-n-5n= | | 2(2x-3)=2(4x+3) | | 10-6v=-50 | | 123456789a=9999994758565657473727388928828281818177273738848485858588585 | | 2+54x^3=0 | | Ix+11I-2=0 | | 5p-2=-p+4 | | -34-4x=-7x+14 | | b(b)=-3b | | x+32-24=45 | | 4x-3.72=60 | | 6y-9=14y+7 | | 7x-6=42-5x | | 100a=193748563646564646465646565656 | | 5a-3=5a+4 | | y=-12x-x+20 | | (-5)x(-8)(-9)= | | 6x^2+3=-102 | | 4x+12=-3x+-9 | | 432=36b | | y-84=10.25 | | X-123=77-9x | | 6x+7=8-15 | | (+5)+(+12)+(+17)= | | 9r^2+3=48 | | 436+w=600 | | 70=0.6r | | c^2+12c+36-q^2= | | F(x)x=2.4 | | z+48=136 |